Digital marketing plan for ASSETFLOOW STARTUP - Filipe, Joana Soares de La Cerda (My University, 2024)
The main aim of this project is to draw up a proposal for a digital marketing plan for a B2B market for AssetFloow, a company operating in the retail sector. The need for this digital marketing plan arises from the absence of an active digital marketing strategy which is a critical gap recognising the role of digital presence in contemporary organisational success. This study emphasizes the necessity for AssetFloow to leverage digital tools. The business and software industry are witnessing a growing trend towards digitalization, and companies like AssetFloow need to strategically adopt digital tools to differentiate themselves from competitors. In order to develop a comprehensive digital marketing plan, it was essential to collect data. This entailed conducting three semi-structured interviews as the primary data source with two potential clients of AssetFloow and one with a marketing specialist, and as a secondary data source, conducting online research. After collecting and analysing this information, it was possible to understand the importance of a digital marketing plan and which communication channels are most efficient to B2B audience. Subsequently, the digital marketing plan was planned, starting with an analysis of the current situation, defining objectives, strategy, and the plan's areas of focus, and ending with the definition of tactics to be applied in each area, along with action scheduling, and methods of evaluation and control. Through the implementation of this plan, the aim is to increase AssetFloow brand awareness and establish the company as a specialist in the area.

O presente projeto tem como principal objetivo elaborar uma proposta de plano de marketing digital para um mercado B2B para a AssetFloow, uma empresa que opera no sector do retalho. A necessidade deste plano de marketing digital surge da ausência de uma estratégia ativa de marketing digital, o que constitui uma lacuna crítica, reconhecendo o papel da presença digital no sucesso das organizações contemporâneas. Este estudo sublinha a necessidade de a AssetFloow tirar partido das ferramentas digitais. A indústria empresarial e de software assiste a uma tendência crescente para a digitalização, e empresas como a AssetFloow precisam de adotar estrategicamente ferramentas digitais para se diferenciarem da concorrência. Para desenvolver um plano de marketing digital abrangente, era essencial recolher dados. Para o efeito, foram realizadas três entrevistas semiestruturadas como fonte de dados primária, com dois potenciais clientes da AssetFloow e uma com um especialista em marketing, e como fonte de dados secundária, a realização de pesquisas online. Após a recolha e análise desta informação, foi possível compreender a importância de um plano de marketing digital e quais os canais de comunicação mais eficientes para o público B2B. Posteriormente, foi desenvolvido o plano de marketing digital, começando pela análise da situação atual, definindo os objetivos, a estratégia e as áreas de enfoque do plano, e terminando com a definição das táticas a aplicar em cada área, bem como a calendarização das ações e os métodos de avaliação e controlo. Com a implementação deste plano, pretende-se aumentar a notoriedade da marca AssetFloow e afirmar a empresa como especialista na área.
Keywords: Internship report; Digital marketing; Digital marketing plan; Social Media; B2B Startup